Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 97620 by mathmax by abdo last updated on 08/Jun/20

calculate ∫_0 ^∞  ((sin(πx^2 ))/(x^4 −x^2 +1))dx

calculate0sin(πx2)x4x2+1dx

Answered by mathmax by abdo last updated on 10/Jun/20

let I =∫_0 ^∞  ((sin(πx^2 ))/(x^4 −x^2  +1))dx ⇒2I =∫_(−∞) ^(+∞)  ((sin(πx^2 ))/(x^4 −x^2 +1))dx =Im(∫_(−∞) ^(+∞)  (e^(iπx^2 ) /(x^4 −x^2  +1))dx)  let ϕ(z) =(e^(iπz^2 ) /(z^4 −x^2  +1))  poles of ϕ?  z^4 −z^2  +1 =0⇒t^2 −t +1 =0   (t=z^2 )  Δ =−3 ⇒t_1 =((1+i(√3))/2) =e^((iπ)/3)  and t_2 =((1−i(√3))/2) =e^(−((iπ)/3))  ⇒  ϕ(z) =(e^(iπz^2 ) /((z^2 −e^((iπ)/3) )(z^2 −e^(−((iπ)/3)) ))) =(e^(iπz^2 ) /((z−e^((iπ)/6) )(z+e^((iπ)/6) )(z−e^(−((iπ)/6)) )(z+e^(−((iπ)/6)) )))  residus theorem give   ∫_(−∞) ^(+∞)  ϕ(z)dz =2iπ{ Res(ϕ,e^((iπ)/6) ) +Res(ϕ,−e^(−((iπ)/6)) )}  Res(ϕ,e^((iπ)/6) ) =lim_(z→e^((iπ)/6) )   (z−e^((iπ)/6) )ϕ(z) =(e^(iπe^((iπ)/3) ) /(2e^((iπ)/6) (2isin((π/3))))) =(e^(iπ((1/2)+((i(√3))/2))) /(4i×((√3)/2))) e^(−((iπ)/6))   =(1/(2i(√3))) e^(−((iπ)/6))   i .  e^(−((π(√3))/4))  =(1/(2(√3))) e^(−((π(√3))/4))  e^(−((iπ)/6))   Res(ϕ,−e^(−((iπ)/6)) ) =(e^(iπe^(−((iπ)/3)) ) /(−2e^(−((iπ)/6)) (−2i sin((π/3))))) =(1/(4i×((√3)/2))) e^((iπ)/6)   e^(iπ((1/2)−((i(√3))/2)))   =(1/(2i(√3))) .i .e^((π(√3))/4)  e^((iπ)/6)  =(1/(2(√3))) e^((π(√3))/4)  e^((iπ)/6)  ⇒  ∫_(−∞) ^(+∞)  ϕ(z)dz =2iπ{ (1/(2(√3))) e^(−((π(√3))/4)) e^(−((iπ)/6))  +(1/(2(√3))) e^((π(√3))/4)  e^((iπ)/6) }  =((iπ)/(√3)){ e^(−((π(√3))/2))  (((√3)/2)−(i/2)) +e^((π(√3))/4) (((√3)/2)+(i/2))}  =((iπ)/(√3)){ ((√3)/2) e^(−((π(√3))/4))  −(i/2) e^(−((π(√3))/4))  +((√3)/2) e^((π(√3))/4)  +(i/2) e^((π(√3))/4)  }  =((iπ)/2) e^(−((π(√3))/4))  +((iπ)/2) e^((π(√3))/4)  +(...) ⇒Im(∫_(−∞) ^(+∞)  ϕ(z)dz =(π/2) (e^((π(√3))/4)  +e^(−((π(√3))/4)) ) =2I ⇒  ★I =(π/4)( e^((π(√3))/4)  +e^(−((π(√3))/4)) )★

letI=0sin(πx2)x4x2+1dx2I=+sin(πx2)x4x2+1dx=Im(+eiπx2x4x2+1dx)letφ(z)=eiπz2z4x2+1polesofφ?z4z2+1=0t2t+1=0(t=z2)Δ=3t1=1+i32=eiπ3andt2=1i32=eiπ3φ(z)=eiπz2(z2eiπ3)(z2eiπ3)=eiπz2(zeiπ6)(z+eiπ6)(zeiπ6)(z+eiπ6)residustheoremgive+φ(z)dz=2iπ{Res(φ,eiπ6)+Res(φ,eiπ6)}Res(φ,eiπ6)=limzeiπ6(zeiπ6)φ(z)=eiπeiπ32eiπ6(2isin(π3))=eiπ(12+i32)4i×32eiπ6=12i3eiπ6i.eπ34=123eπ34eiπ6Res(φ,eiπ6)=eiπeiπ32eiπ6(2isin(π3))=14i×32eiπ6eiπ(12i32)=12i3.i.eπ34eiπ6=123eπ34eiπ6+φ(z)dz=2iπ{123eπ34eiπ6+123eπ34eiπ6}=iπ3{eπ32(32i2)+eπ34(32+i2)}=iπ3{32eπ34i2eπ34+32eπ34+i2eπ34}=iπ2eπ34+iπ2eπ34+(...)Im(+φ(z)dz=π2(eπ34+eπ34)=2II=π4(eπ34+eπ34)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com